2006
DOI: 10.1007/s00412-006-0063-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA underreplication in intercalary heterochromatin regions in polytene chromosomes of Drosophila melanogaster correlates with the formation of partial chromosomal aberrations and ectopic pairing

Abstract: We studied the influence of the Suppressor of Underreplication (SuUR) gene expression on the intercalary heterochromatin (IH) regions of Drosophila melanogaster polytene chromosomes. We observed a strong positive correlation between increased SuUR expression, underreplication extent, amount of DNA truncation, and formation of ectopic contacts in IH regions. SuUR overexpression from heat shock-driven transgene results in the formation of partial chromosomal aberrations whose breakpoints map exclusively to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 29 publications
6
33
0
Order By: Relevance
“…The same effect was observed upon daily heat-shock induced overexpression of GAL4-HP1 (Table 1). It should be mentioned that a daily heat-shock treatment per se neither alters the frequency of breaks in intercalary heterochromatin (Table 1) nor affects UR (Belyaeva et al, 2006). Using quantitative Southern blot hybridization as well as in-gel hybridization, we demonstrated that DNA polytenization of the abd-A gene located in the zone of UR in the region 89E (Belyakin et al, 2005;Moshkin et al, 2001) is increased 4.3-fold by daily heat-shock induction of the hs-HP1 expression (Fig.…”
Section: Overexpression Of Hp1 Displaces Suur From Chromosomesmentioning
confidence: 82%
See 1 more Smart Citation
“…The same effect was observed upon daily heat-shock induced overexpression of GAL4-HP1 (Table 1). It should be mentioned that a daily heat-shock treatment per se neither alters the frequency of breaks in intercalary heterochromatin (Table 1) nor affects UR (Belyaeva et al, 2006). Using quantitative Southern blot hybridization as well as in-gel hybridization, we demonstrated that DNA polytenization of the abd-A gene located in the zone of UR in the region 89E (Belyakin et al, 2005;Moshkin et al, 2001) is increased 4.3-fold by daily heat-shock induction of the hs-HP1 expression (Fig.…”
Section: Overexpression Of Hp1 Displaces Suur From Chromosomesmentioning
confidence: 82%
“…However, the frequencies of chromosomal breaks, which reflect the degree of UR, observed in a number of marker intercalary heterochromatin regions in Su ( those in the wild-type Oregon R strain ( Table 1). Given that the formation of chromosomal breaks is determined during the early embryonic development (Belyaeva et al, 2006;Makunin et al, 2002), it is likely that Su(var)2-5 03 /Su(var)2-5 05 heterozygotes embryos have enough maternally supplied HP1 to recruit SUUR to chromosomes. Thus, our data suggest that HP1 is required for SUUR association with chromosomes.…”
Section: Suur Does Not Bind To Chromosomes In Su(var)2-5 Mutantsmentioning
confidence: 99%
“…Incomplete chromosome replication is rarely considered as a mechanism responsible for chromosome nondisjunction during cell division (44), because cells with underreplicated DNA should not enter anaphase due to the activity of DNA integrity checkpoints (45,46). However, the rDNA locus in budding yeast stands out in this respect, as it has persistent DSBs (47), which apparently do not trigger a checkpoint response, because nucleolar chromatin is shielded from DNA damage checkpoint signaling (48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in SuUR gene copy number results in stronger underreplication. 10,12 When GAL4-UAS system is used to overexpress SUUR in mid-third instar salivary glands (via Sgs3-GAL4 driver), polytene chromosomes must face a large excess of SUUR protein. This overexpression affects the morphology of polytene chromosomes, causing the so-called "swellings"-reversible thickenings of chromosome in the IH and PH regions-to form.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…8 DNA molecules that failed to complete replication have free termini that can be joined, and this process is thought to cause formation of ectopic contacts between IH bands and between IH and PH regions. [9][10][11] It is the mere presence and amount of SUUR protein that determines the extent of underreplication and formation of ectopic contacts in IH of salivary gland polytene chromosomes.…”
Section: Introductionmentioning
confidence: 99%